Analisis Pengaruh Kompensasi Terhadap Kinerja Pegawai Dengan Kepuasan Kerja Sebagai Variabel Intervening(Studi Kasus pada Kantor Pelayanan Pajak Pratama Karanganyar) - Khumaini, Alfan, Ihwan Susilo, SE.,M.Si., Ph.D, Drs. M. Farid Wajdi, Ph.D (2017)
The purpose of this research is to analyze the effect of compensation, job satisfaction, and employee performance. Job satisfaction variable has a mediating role in the relationship between compensation and performance of employees. The type of this research will be using a cross-sectional study, to determine the dynamics of the correlation between variables tested. In this study uses quantitative analysis method utilizing the primary data obtained from 98 respondents in Karanganyar Pratama Tax Office. Data were analyzed by linear regression analysis to determine the relationship between variables and its role as a form of mediation between variables. The level of significance between variables were measured using the t test, whereas in the intervening test used Sobel test. Variables examined the extent of the compensation, job satisfaction and employee performance. The results of this study can be explained that compensation has a significant impact on job satisfaction. Job satisfaction also has a significant influence on employee performance. Therefore, the compensation does not have a direct influence on the performance of employees, so job satisfaction has a role as an intervening with full model of mediation in the relationship between compensation and performance of employees.